In vitro and in silico studies of bis (indol-3-yl) methane derivatives as potential α-glucosidase and α-amylase inhibitors - Peng-Fei Zheng; Zhuang Xiong; Cui-ying Liao; Xin Zhang; Mei Feng; Xiao-Zheng Wu; Jing Lin; Lin-Sheng Lei; You-Cheng Zhang; Shao-Hua Wang; Xue-Tao Xu (Taylor & Francis Group, 2021)
In this paper, bis (indol-3-yl) methanes (BIMs) were synthesised and evaluated for their inhibitory activity against α-glucosidase and α-amylase. All synthesised compounds showed potential α-glucosidase and α-amylase inhibitory activities. Compounds 5 g (IC50: 7.54 ± 1.10 μM), 5e (IC50: 9.00 ± 0.97 μM), and 5 h (IC50: 9.57 ± 0.62 μM) presented strongest inhibitory activities against α-glucosidase, that were ∼ 30 times stronger than acarbose. Compounds 5 g (IC50: 32.18 ± 1.66 µM), 5 h (IC50: 31.47 ± 1.42 µM), and 5 s (IC50: 30.91 ± 0.86 µM) showed strongest inhibitory activities towards α-amylase, ∼ 2.5 times stronger than acarbose. The mechanisms and docking simulation of the compounds were also studied. Compounds 5 g and 5 h exhibited bifunctional inhibitory activity against these two enzymes. Furthermore, compounds showed no toxicity against 3T3-L1 cells and HepG2 cells.Highlights A series of bis (indol-3-yl) methanes (BIMs) were synthesised and evaluated inhibitory activities against α-glucosidase and α-amylase. Compound 5g exhibited promising activity (IC50 = 7.54 ± 1.10 μM) against α-glucosidase. Compound 5s exhibited promising activity (IC50 = 30.91 ± 0.86 μM) against α-amylase. In silico studies were performed to confirm the binding interactions of synthetic compounds with the enzyme active site.